US oil strategy in the Caspian Basin: Hegemony through interdependence. (June 2014) - Raphael, Sam; Stokes, Doug
President Obama has continued to emphasise the strategic importance of stable energy supplies to US national security interests, with the oil-rich Central Asian region a key part of global energy markets. This region has seen significant economic and strategic inroads by the United States over the last decade in a broad attempt to integrate it within the US-led liberal order. This article examines these policy developments and draws upon theoretical debates on US grand strategy to argue that, rather than necessarily signalling increasing geopolitical rivalry with other powers such as China and Russia, US policy is designed primarily to incorporate the region through deepening market interdependence. As such, while there is a complex mix of geopolitical rivalry and economic interdependence developing in the Caspian, even in the face of purported US decline and increase of its domestic supplies through fracking, Washington remains committed to acting as a hegemonic stabiliser in the Caspian.